Catalytic Nitrate Removal in a Trickle Bed Reactor: Direct Drinking Water Treatment. Issue 5 (1st May 2017) - Bertoch, Madison; Bergquist, Allison M.; Gildert, Gary; Strathmann, Timothy J.; Werth, Charles J.
Abstract : Palladium (Pd)‐based catalysts hold promise as an alternative water treatment technology for nitrate (NO3 ), but practical application requires a flow‐through reactor that efficiently delivers hydrogen (H2 ) from gas to water. A trickle bed reactor (TBR) packed with a 0.1 percent by weight (wt%) Pd–0.01 wt% In/γ‐Al2 O3 (indium and porous aluminum oxide) catalyst was evaluated to address this challenge. Catalytic activity generally increased with H2 superficial velocity (0.65–29.6 m/h) and liquid (deionized water) superficial velocities from 14.8 to 26.6 m/h before decreasing at 38.5 m/h. This decrease corresponded to a change in flow regime and suggests that optimal TBR performance occurs at the transition from pulse to bubble flow. An optimal TBR activity of 19.5 ± 1.3 mg NO3 /min‐g Pd was obtained; this is only 18% of the batch reactor activity as a result of H2 mass transfer limitations, but three to 15 times greater than activities obtained with previous flow‐through reactors. Catalyst deactivation occurred in the TBR after 41 days of operation, motivating the need for improved fouling mitigation strategies.